2011
DOI: 10.3171/2011.3.focus1136
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in computed tomography perfusion: implications for acute stroke management

Abstract: Object Although dynamic, first-pass cerebral CT perfusion is used in the evaluation of acute ischemic stroke, a lack of standardization restricts the value of this imaging modality in clinical decision-making. The purpose of this study was to comprehensively review the reported sources of variability and error in cerebral CT perfusion results. Methods A systematic literature review was conducted, 120 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…12 Previous published studies showed that even minor variations in the user-defined inputs in venous ROI placement or in pre-and postenhancement cutoff values significantly changed quantitative perfusion parameter values. [45][46][47] This may cause variability of perfusion results, even when the same data are repetitively processed by the same observer. Using custom-designed perfusion analysis software in which the users have full control may reduce these variations and their influence on differences in the resulting perfusion parameters.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous published studies showed that even minor variations in the user-defined inputs in venous ROI placement or in pre-and postenhancement cutoff values significantly changed quantitative perfusion parameter values. [45][46][47] This may cause variability of perfusion results, even when the same data are repetitively processed by the same observer. Using custom-designed perfusion analysis software in which the users have full control may reduce these variations and their influence on differences in the resulting perfusion parameters.…”
Section: Discussionmentioning
confidence: 99%
“…One reason could be the lack of a standardized imaging approach. Variation in the imaging technique as well as vendor software highlights this limitation 20 21. Second, imaging represents a snapshot in time in an otherwise complicated and rapidly evolving process.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] While advanced imaging techniques hold promise for the evaluation of patients with acute ischemic stroke, there is variation in techniques and definitions of parameters that limit wide application and acceptance of these techniques. 4,[23][24][25] There is currently no consensus on a standard imaging approach for acute ischemic stroke. We studied a large data base of hospitals in the United States to assess the recent use of advanced imaging in patients with acute ischemic stroke treated with intravenous thrombolysis, including an evaluation of the use of advanced imaging, with respect to patient outcome.…”
mentioning
confidence: 99%